Cryopreserved Cord Blood Preparations in Combined Surgical Treatment of Purulent Complications of Type II Diabetes mellitus - Popovych, Yaroslav O. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2014)
Diabetic foot syndrome (DFS) is a serious late complication of Diabetes mellitus (DM) and the unsolved problem of endocrine surgery. This pathology occurs in 80% of patients with diabetes and half of them leads to an extremity amputation. Combined drug and surgical treatment of patients with type II diabetes complications with pyonecrotic DFS stages and sacrococcygeal and perineum phlegmons was analysed. There were used the medical immune biological preparations (MIBP) based on cryopreserved placental blood which contribute to the normalization of immunological reactions, proliferation processes, stimulate a reparation, possess antioxidant, adaptogenic, anti-hypoxic, anabolic and anti-inflammatory effects. The patients were administered with "Cryocell-Cryocord", i.e. placental blood serum (108 patients), and in severe endointoxication they were additionally treated within "Cryocell-Hemocord", placental blood leukoconcentrate (37 patients). When applying MIBP the insulin dosage is reduced by 25-30%. A significant decrease in leukocyte index, the level of an average molecular weight peptides is observed. Cytoarchitecture of erythrocytes significantly improved. Potentiation of the preparations on the activity of metalloenzymes, hepatocyte cytolysis enzymes was found. The number of proteases inhibitors decreases with a parallel increase in the content of albumin, total protein amount, normalization of organ specific enzymes.The increase in total content of immunoglobulins, a sharp decline in the level of circulating immune complexes (antigen-antibody autoantigens) with a parallel increase in the antibodies of natural protection were revealed. In addition, under the influence of cord blood MIBP the wound cleansing and its healing starts faster, pyo-inflammatory process is restricted at the foot level, lower leg edema disappears. The data obtained can be interpreted as recovery of reparative processes in the wound due to effective correction of metabolic-homeostatic changes in the patient suffering from diabetes and its complications.Probl Cryobiol Cryomed 2014; 24(4):332-345.